The experience of flow during sensorimotor synchronization to musical rhythms. (September 2019) - Stupacher, Jan
Sensorimotor integration tasks, such as body movements in time with music, can foster the experience of flow – a pleasurable state of full engagement and concentration occurring during a seemingly effortless and automatic activity. As it can be argued that both music and flow are embodied phenomena, perception-action coupling might be the core of the intimate relationship between flow and music. The current study examines the relationship between the subjective experience of flow and sensorimotor synchronization accuracy/stability in a finger-tapping task with music. In a between-subjects design, participants tapped in time with the beat of music clips with either low, medium, or high rhythmic complexity. After the tapping task, they rated their flow state on the Flow Short Scale with the two subscales fluency of performance and absorption by activity . Tapping accuracy and stability were assessed by the circular variance and the SD of inter-tap-intervals (ITIs), respectively. Both tapping accuracy and stability were significantly correlated with fluency of performance for music clips with medium and high rhythmic complexity, but not for music clips with low rhythmic complexity. No significant correlations were found between tapping accuracy/stability and absorption by activity . The findings add to evidence that perception-action coupling plays a key role in explaining the relationship between flow experience and musical activities. They also suggest that absorption by activity is not as relevant to the experience of flow during musical activities as one might initially assume.